A blood-based transcriptomic signature stratifies severe Crohn’s disease and defines potentially targetable therapeutic pathways - Gonsky, Rivkah; Adams, Evan; Potdar, Alka A.; Botwin, Gregory; Biener-Ramanujan, Eva; McGovern, Dermot P. B.; Braun, Jonathan G.; Fleshner, Phillip; Targan, Stephan R. (Frontiers in Gastroenterology, 2023)
Introduction Despite advances in medical therapy, many patients with Crohn’s disease (CD) ultimately require surgery for disease management. Identifying the underlying molecular pathways for subgroup stratification is critical to the improvement of prognostics and therapeutics and to biomarker discovery. Methods We purified CD3+ T cells from the paired blood and mucosa samples of 100 CD and 17 non-inflammatory bowel disease (IBD) subjects requiring surgery. Longitudinal samples (n = 49) were collected 4–13 months postoperatively. Results Transcriptional profiling at the time of surgery revealed two CD patient subgroups: the CD-PBT subgroup, which was clustered tightly with non-IBD subjects, and the CD-PBmu(cosal) subgroup, which shifted from peripheral toward a mucosal-like expression profile. The CD-PBmu subgroup was characterized by differential gene expression, elevated genetic transcriptional risk score (TRS), and a distinct T-cell subset composition associated with perianal-penetrating/stricturing disease, post-surgical recurrence, and immunoreactivity to multiple microbial antigens. CD-PBmu subtyping was validated in a CD cohort in whom anti-TNF therapy had been unsuccessful. The CD-PBmu subgroup, in contrast to the CD-PBT subgroup, was distinguished by decreased pro-inflammatory cytokine/chemokine and adhesion molecule expression postoperatively. For clinical translation, we identified a CD-PBmu 42-gene classifier associated with a TRS signature, clinical severity markers, and underlying protein kinase signaling pathways to identify therapeutic targets. Discussion The CD-PBmu signature holds potential for future investigation to improve accuracy in identifying a subset of patients with severe CD who may benefit from early initiation of therapeutics to defined molecular pathways.